Pollen morphology and viability relates to seed productionin hybrid roses - Nadeem, Muhammad; Akond, Masum; Riaz, Atif; Qasim, Muhammad; Younis, Adnan; Farooq, Amjad (Plant Breeding and Seed Science, 2013)
To avoid the risk of very low seed production, the estimation of the pollen fertility is the reliable tool. In the present study nine hybrid rose genotypes were evaluated for their pollen viability and fertility status in vitro. The strength of contribution of each cultivar as a male parent was evaluated in the field. Successful crossing %age was correlated with the pollen germination %age and pollen tube length of each male parent cultivars in controlled conditions. Pollen vigor parameters indicated great variations in pollen quality, quantity, and viability and germination % ages. On average basis the performance of the cultivar Angel Face and Handel was better with respect to both number of anther per flower and number of pollens per anther. Pollen size (L: D) was almost same in all cultivars hence no significant differences were observed. Comparison of means of viability %age revealed that maximum number of viable pollens in term of viability %age were possessed by cultivar Handel (70%) followed by ‘Gruss an Teplitz’ (64%). The minimum viability of pollens was exhibited by the Cultivar ‘Autumn Sunset’ having pollen viability of 35%. A strong correlation among pollen germination %age and pollen tube length (r = 0.77) and pollen germination %age and pollen viability %age (r = 0.731) was exhibited. Pollen germination is also strongly correlated with pollen size (r =0.738) The comparison of various fertility parameters in vitro and in vivo revealed that cultivar “Handel” showing its maximum pollen viability in vitro performed well to get more crossing success in the field .